2000
DOI: 10.1002/(sici)1099-1387(200005)6:5<217::aid-psc242>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity comparison of a multi-antigenic peptide bearing V3 sequences of the human immunodeficiency virus type 1 with TAB9 protein in mice

Abstract: The multiple antigenic peptide system (MAP) has been proposed as a novel and valuable approach for eliciting antibodies for peptides and developing synthetic vaccines. Multi-epitope polypeptides (MEP) have also been developed as an alternative to the recombinant approach for vaccines. The V3 loop from the HIV type 1 (HIV-1) external glycoprotein (gp120) contains the principal neutralization domain (PND). Antibodies against this region neutralize HIV-1 in vitro and in vivo. In this work, a novel presentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…We have previously shown that V3 cocktails with MAPs are a good strategy to present epitopes to the immune system [25]. In the context of this study we have demonstrated other possibilities.…”
Section: Numbersupporting
confidence: 51%
See 2 more Smart Citations
“…We have previously shown that V3 cocktails with MAPs are a good strategy to present epitopes to the immune system [25]. In the context of this study we have demonstrated other possibilities.…”
Section: Numbersupporting
confidence: 51%
“…The JY1-peptide and MAP were synthesized following procedures described elsewhere [25]. The B-cell epitope comprised the central 15 aa from V3 regions of gp120 of HIV-1 isolates: JY1, subtype D (RQSTPIGLGQALYTT).…”
Section: Syntheses Of Peptide and Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these strategies have relied on the use of combinations of several representa- tive peptide variants. We had earlier shown that V3 loopbased peptide cocktails, in the form of MAP dendrimers, were a good strategy of epitope presentation (9).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TAB9, which includes six V3 loop peptides (isolates LR150, JY1, RF, MN, IIIB, and BRVA), was used in a phase I clinical study (8). The recombinant protein was immunogenic and induced high levels of antibody neutralization, but the immune response was mainly directed at JY1 and LR150 and only weakly at MN, suggesting the need for considerable improvement (9). The problem with chimeric polypeptides of this type is that they adopt unpredictable 3D structures that favor the exposure of some epitopes, at the expense of others that in practice remain silent.…”
Section: Introductionmentioning
confidence: 99%